‘Optimus Civis. A Model Citizen and Ruler of Rome in the Republican and Imperial Periods’: Introduction - Appel, Hanna; Wojciechowski, Przemysław (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2021)
Introduction to an issue.